A STUDY ON SOCIAL MEDIA MARKETING: A STRATEGIC TOOL TO ANALYZE CONSUMER BUYING BEHAVIOUR DURING THE PANDEMIC - Ms Tejaswini S; Ms Brinda M (The journal of contemporary issues in business and government, 2022)
Social media has been broadly used to search for data and have hypnotised the population to assemble data concerning COVID pandemics from various perspectives. During this lockdown, individuals are constrained to stay at home and social media has maintained care and upheld mindfulness and pandemic updates. On this note, social media marketing has been a significant subject of conversation during this pandemic. Social media marketing is an amazing route for associations to anive at prospects and customers. The most prominent and more associated with people is utilizing social media networks, the less complex it will be for the organization to achieve every other promoting objective on the rundown. Today, more than later in continuous history, social media platforms have become the basic wellspring of information beating print and other computerized media stages. The persistent COVID-19 pandemic influences each part of our lives, from how individuals contribute their energy, search, find, and buy things, to the way organizations, brands, and sponsors/advertisers broadcast and promote their products or services. At the point when people began contributing more energy at home, due to pandemics, they furthermore began using the web more, which achieved an abrupt extension in web-based media engagement. Keeping this as a focus, the current study shows how well social media marketing can help analyse customers’ buying behaviour, especially during this great pandemic.